PENGARUH MEDIA SOSIAL TERHADAP PENYIMPANGAN PERILAKU REMAJA (CYBERBULLYING) - Dinar Primasti; Sulih Indra Dewi (Universitas Tribhuwana Tunggadewi, 2017)
Abstract: The access to internet today is not merely to interact with other people, but also to socialize so the user will have a close relation with the real world. Facebook is one of social media which grows significantly nowdays. This research aimed to find out the effect of social media, facebook precisely to the misbehavior among teenagers. The focus of this research was the cyberbullying by teenagers which recently happens quite often. The method of this research is quantitative and involved students from High Schools and Vocational High Schools in Malang. The research showed a significant correlation between the using of facebook with the cyberbullying among teenagers in Malang. Keywords: Social Media, Cyberbullying, Facebook.